Analisis Kinerja Keuangan BLUD Pada Rumah Sakit X Di Provinsi Kalimantan Selatan (KALSEL) - Vitasari, Anastasia; Hasymi, Liana Fitriani; Marliadi, Reny; Rahman, Andri Nur; Hastuti, Eny (Magister Ilmu Akuntansi Universitas Jambi, 2025)
Financial performance is an important indicator in assessing the efficiency and effectiveness of hospital financial management, especially those with Regional Public Service Agency (BLUD) status. This research aims to analyze the financial performance of Hospital The research method used is descriptive quantitative with data collection through financial report documentation for the 2019–2023 period and interviews. Analysis was carried out on liquidity ratios, activity, profitability, PNBP ratio to operational costs, as well as BLUD financial management compliance. The research results show that overall Hospital The conclusion of this research is that although Hospital X has demonstrated good financial performance according to regulatory standards, improvements in certain aspects are still needed to support financial management.